(untitled) (World Bulletin of Management and Law, 2024)
In the modern world, the study of the legal systems of different countries in the context of international experience is becoming increasingly relevant This article is devoted to a comparative analysis of the criminal law aspects of intentional grievous bodily harm in the Republic of Uzbekistan and foreign countries. The author of the article examines the norms of the Criminal Code of the Republic of Uzbekistan defining such crimes and compares them with approaches and standards applied in other countries. The analysis allows us to identify general trends and unique features of the criminal legislation of Uzbekistan in this area. Special attention is paid to the issues of qualification of crimes, types of responsibility and penalties applied. A comparative analysis of the legislation and practice of other countries allows the author of the article to draw conclusions about possible ways to improve the criminal justice system in the Republic of Uzbekistan. The results of the study can be used to develop proposals for amendments and additions to the current legislation